Two matrices are equal if and only if the matrices have the same shape and elements in corresponding positions are equal.
Example 1 :
If
find p, q, r and s.
Solution :
Both are 2x 2 matrices, so they are equal and their corresponding terms will be equal.
By equating corresponding terms, we get
p = 9 |
q+1 = -2 q = -2-1 q = -3 |
r2 = 4 r = √4 r = ±2 |
5 = s s = 5 |
So, the values of p, q, r and s are 9, -3, ±2 and 5 respectively.
Example 2 :
Solution :
By equating corresponding terms, we get
a = 1, b = -5, c = 2 and d = 3.
Example 3 :
Solution :
By equating corresponding terms, we get
x = -2
a = 5
2a = b
By applying the value of a in 2a = b, we get
2(5) = b
b = 10
So, the value of x is -2, a = 5 and b = 10.
Example 4 :
Solution :
By equating corresponding terms, we get
x = 4
1-y = 0
y = 1
z = -2
So, the value of x is 4, y = 1 and z = -2.
Example 5 :
Solution :
x2 = 9
x = ±3
But equating x-1 to 2, we get
x = 3
y = -y y+y = 0 2y = 0 y = 0 |
z = z2 z2 - z = 0 z(z-1) = 0 z = 0 and z = 1 |
So, the value of x is 3, y = 0 and z = 0 or 1.
Example 6 :
Solution :
By multiplying 1 x 2 by 2 x 2, we get 1 x 2 matrix.
= [2x-9 4x + 0]
= [2x - 9 4x]
Now we have to multiply 1 x 2 by 2 x 1, we get 1 x 1 matrix.
= x(2x - 9) + 8(4x)
= 2x2 - 9x + 32x
= 2x2 + 23x
2x2 + 23x = 0
x(2x + 23) = 0
x = 0 and 2x = -23
x = -23/2
So, the required values of x are 0 and -23/2.
Example 7 :
Solution :
All three matrices are with the same order, 2 x 2. By combining the corresponding terms, we get
2 - 4 = x -----(1)
2 - (-1) = y -----(2)
6 - 5 = z ------(3)
From (1), -2 = x, then x = -2
From (2), 2 + 1 = y, then y = 3
From (3), 6 - 5 = z, then z = 1
So, the values of x, y and z are -2, 3 and 1 respectively.
Example 8 :
Solution :
By equating the corresponding terms, we get
2 = 4x - 6
4x = 2 + 6
4x = 8
x = 8/4
x = 2
So, the required value of x is 2.
Example 9 :
Solution :
Solving for b,
4b + 2 = 11
4b = 11 - 2
4b = 9
b = 9/4
Solving for c,
-3 = -2c - 1
-3 + 1 = -2c
-2c = -2
c = 1
Solving for d,
4d = 0
d = 0/4
d = 0
Solving for a,
-4a = -8
a = 8/4
a = 2
Solving for f,
2f - 1 = 0
2f = 1
f = 1/2
Solving for g,
-14 = -3g - 2
-14 + 2 = -3g
-3g = -12
g = 12/3
g = 4
So, the values of a = 2, b = 9/4, c = 1, d = 0, f = 1/2 and g = 4.
Example 10 :
Solution :
4c = 2c + 5
4c - 2c = 5
2c = 5
c = 5/2
Solving for d,
2 - d = 4d
2 = 4d + d
5d = 2
d = 2/5
solving for h,
By comparing the corresponding terms, h = -1
Solving for g,
By comparing the corresponding terms, we get
g = 5
Solving for f,
f - g = 2
By applying the value of g, we get
f - 5 = 2
f = 2 + 5
f = 7
Solving for c,
-10 = -4c
c = 10/4
c = 5/2
Example 11 :
Find the values of a and b if A = B where
Solution :
By equating the corresponding terms, we get
a + 4 = 2a + 2 a - 2a = 2 - 4 -a = -2 a = 2 |
3b = b2 + 2 b2 - 3b + 2 = 0 (b - 2)(b - 1) = 0 b = 2 and b = 1 |
-6 = b2 - 5b
b2 - 5b + 6 = 0
(b - 3)(b - 2) = 0
b = 3 and b = 2
So, the value of a = 2 and the values of b are 1, 2, 3.
Kindly mail your feedback to v4formath@gmail.com
We always appreciate your feedback.
©All rights reserved. onlinemath4all.com
Feb 10, 25 07:03 AM
Feb 10, 25 07:01 AM
Feb 10, 25 06:59 AM